До питання про формування інсулінорезистентності у підлітковому віці - Хижняк, О. О.; Сулима, Т. Н.; Черевко, І. Г. (Clinical Endocrinology and Endocrine Surgery, 2008)
System analysis of some hormonal effects on insulin sensitivity in adolescent boys of 11-17 ages was done. It was determined that insulin resistance index HOMA-IR=3.9 divides sample on sensitive and resistant to insulin individuals. It was shown selective effects of some hormones on insulin stimulated glucose disposal by target tissues: cortisol increases threshold of hepatocytes sensitivity; high concentration of leptin inhibites postprandial glucose uptake by muscles and adipose tissue.